2017
DOI: 10.1038/hdy.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the expected response to genomic selection of individuals and families in Eucalyptus breeding with an additive-dominant model

Abstract: We report a genomic selection (GS) study of growth and wood quality traits in an outbred F hybrid Eucalyptus population (n=768) using high-density single-nucleotide polymorphism (SNP) genotyping. Going beyond previous reports in forest trees, models were developed for different selection targets, namely, families, individuals within families and individuals across the entire population using a genomic model including dominance. To provide a more breeder-intelligible assessment of the performance of GS we calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 54 publications
11
57
0
Order By: Relevance
“…Our findings are also supported by goodness-of-fit values since dominance models are more parsimonious than the additive model. Accordingly, other studies have shown similar empirical results [Resende et al, 2017, Dias et al, 2018. Despite the importance of dominance effect in grain yield, additivity explained a large portion of variance in grain moisture, suggesting that both traits have different genetic architectures.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Our findings are also supported by goodness-of-fit values since dominance models are more parsimonious than the additive model. Accordingly, other studies have shown similar empirical results [Resende et al, 2017, Dias et al, 2018. Despite the importance of dominance effect in grain yield, additivity explained a large portion of variance in grain moisture, suggesting that both traits have different genetic architectures.…”
Section: Discussionsupporting
confidence: 69%
“…This source of genetic variation was neglected for different reasons, including the lack of informative pedigrees, computational complexities related to estimation of dominance effects [Vitezica et al, 2013], the thought that most genetic variance is additive [Hill, 2010] or can be captured with additive parameterizations [Huang and Mackay, 2016], and the fact that even when non-additive effects are included in the models they are not easily partitioned from additive effects [Muñoz et al, 2014]. Nonetheless, recent inclusion of non-additive effects have demonstrated increased prediction accuracies in some traits in animal and plant breeding [Technow et al, 2014, de Almeida Filho et al, 2016, dos Santos et al, 2016, Resende et al, 2017, Dias et al, 2018 In addition to the source of genetic variability controlling a trait of interest, a second relevant issue to plant breeders is how to manage the challenges of genotype-by-environment (G×E) interaction. G×E interactions are expressed as changes in the relative performance of genotypes across environments, which can affect the genotype ranking.…”
mentioning
confidence: 99%
“…The levels of accuracy which our GP reached are high, and comparable to those that are used to inform selections in crop [46][47][48][49][50] , tree 12,51 and livestock breeding programmes 52,53 . Thus, our results have the potential to increase the speed at which we can successfully breed ash dieback resistant trees.…”
Section: Discussionmentioning
confidence: 59%
“…The levels of accuracy which our GP reached are high, and comparable to those that are used to inform selections in crop 4650 , tree 12,51 and livestock breeding programmes 52,53 . Thus, our results have the potential to increase the speed at which we can successfully breed ash dieback resistant trees.…”
Section: Discussionmentioning
confidence: 56%